(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
With the growth and development of Iraqi cities and the increase in population density in cites’ centers, the development of cities and urban areas involves focus on economic concerns, often resulting in the exclusion of people with disability from participation in meaningful urban activities. In recent decades, technological advances and social awareness have made accessibility more common for people with disability. However, major disparities remain in people’s access to basic support services and opportunities. To ensure that all citizens can benefit from the revitalization of city spaces, it is essential to integrate empowerment strategies for people with disabilities into urban open spaces. The implementation of such strategies can lead to the empowerment of disabled people in urban areas by providing them with access to public spaces, transportation networks, and other services. Therefore, the research problem is concerned with the need to find mechanisms to integrate people with needs into urban spaces through the urban empowerment strategy for people with special needs, and thus revitalize the city’s spaces and achieve a healthy, safe, flexible and sustainable environment. This new design strategy aims to empower and improve the lives of people with diseases, physical disabilities, and mental health impairments by giving them access to social networks, resources, employment opportunities, and leisure activities that enhance the quality of life in cities. It also plays a crucial role in developing an environment that meets the unique financial and personal requirements of disabled people. The paper examines this issue by adopting the descriptive analytical approach, the research employs a questionnaire as a data-gathering technique and the data was analyzed using the Microsoft Excel program. The results showed that there is a clear gap in what is currently provided to disabled people in this city and the development plans for the year 2030. Moreover, the study showed that there are problems in applying empowerment strategies in the development and revitalization of urban spaces.